2019
DOI: 10.5507/bp.2018.082
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory characteristics of enteroviral meningitis in children, including qRT-PCR and sequencing analysis

Abstract: Aims. Enteroviruses (EVs) are the most common agents of aseptic meningitis. Some serotypes can cause serious neuroinfection leading to death. The aim of this study was to determine the representation of EVs in the etiology of aseptic meningitis in children and to analyze the demographic, clinical, laboratory, and epidemiological characteristics of patients with EV meningitis. Patients and Methods. This was a prospective study including 147 patients in three groups: EV meningitis, tick-borne encephalitis, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…We observed a positive correlation between viral load and increased WBC count in infants and children, who also had higher WBC counts compared to preteen‐teenagers and adults. These findings are consistent with previous studies reporting pleocytosis and a median WBC count of approximately 103 cells/mm 3 in individuals with EV meningitis 11,31,32 . Pleocytosis with a predominance of lymphomonocytes and elevated protein levels are indicative of viral infections, but is not sufficient to determine the specific causative agent 31,33 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We observed a positive correlation between viral load and increased WBC count in infants and children, who also had higher WBC counts compared to preteen‐teenagers and adults. These findings are consistent with previous studies reporting pleocytosis and a median WBC count of approximately 103 cells/mm 3 in individuals with EV meningitis 11,31,32 . Pleocytosis with a predominance of lymphomonocytes and elevated protein levels are indicative of viral infections, but is not sufficient to determine the specific causative agent 31,33 .…”
Section: Discussionsupporting
confidence: 89%
“…Although slightly elevated lactate levels have been reported in cases of aseptic meningitis, there is limited research on lactate concentrations in patients with meningitis due to EV infection. A study by Braunova et al 32 reported higher CSF lactate levels in patients with EV meningitis compared to a control group with other CNS infections.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The authors highlighted the possibility that this etiological cause could be more prevalent than currently understood due to the challenges in distinguishing between viral meningitis and encephalitis within this age group 15 . In other published studies, the frequency of male gender in EV meningitis was between 58–71% 4 6 8 16 17 18 19 20 . Similarly, the prevalence of male gender was 74% in our study.…”
Section: Discussionmentioning
confidence: 81%
“…Enteroviruses are the most common pathogen of etiologicallyknown aseptic meningitis in children worldwide [1,[6][7][8]. Many previous studies have been conducted to evaluate the epidemiology of viral meningitis.…”
Section: Discussionmentioning
confidence: 99%